Acknowledging the Effect of “Affect” in Healthcare: Empirical Investigation of Emotional Labor Practices of Physicians During the COVID-19 Pandemic - JAVED, SAMAN; BATOOL, DR NOSHABA (The journal of contemporary issues in business and government, 2021)
Relevance of Affect or Emotions is paramount in front-line jobs. Especially during times like these with the global spread of COVID-19, both mental and physical well-being of healthcare workers are at stake. Having to face hardships of treatment of infected patients, exhausted resources and fear of infection, doctors and paramedical staff need resolute and emotional composure more than ever. Our research aimed to understand the sequential effect of doctors’ emotional job demands on their emotional labor practices at work, emotional exhaustion and well-being. With data gathered from 332 doctors serving in 11 tertiary hospitals across Pakistan, we found that emotional job demands can lower doctors’ subjective, psychological and physical well-being, if they opt to use surface acting at work. However, showing genuine and natural emotions at workplace helps beat emotional exhaustion, thereby increasing the well-being levels. The study contributes to theory and practice by providing a detailed literary examination of emotions in healthcare context and suggesting ways to combat the adversities associated with the affective part of healthcare profession.